2016
DOI: 10.4062/biomolther.2016.026
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-3-O-β-D-Glucuronide Suppresses Lipopolysaccharide-Induced JNK and ERK Phosphorylation in LPS-Challenged RAW264.7 Cells

Abstract: Quercetin, a flavonol, has been reported to exhibit a wide range of biological properties including anti-oxidant and anti-inflammatory activities. However, pharmacological properties of quercetin-3-O-β-D-glucuronide (QG), a glycoside derivative of quercetin, have not been extensively examined. The objective of this study is to elucidate the anti-inflammatory property and underlying mechanism of QG in lipopolysaccharide (LPS)-challenged RAW264.7 macrophage cells in comparison with quercetin. QG significantly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Quercetin suppresses the LPS-induced inflammatory response via various mechanisms [18,22,27,28]; e.g., by inhibiting the NF-κB, STAT-1, and Syk/Src/IRAK-1 pathways. However, little is known about the effect of quercetin on cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin suppresses the LPS-induced inflammatory response via various mechanisms [18,22,27,28]; e.g., by inhibiting the NF-κB, STAT-1, and Syk/Src/IRAK-1 pathways. However, little is known about the effect of quercetin on cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that RAC selectively regulates signaling molecules, ERK and NF-κB. There are some studies showing that selective inhibition of ERK and NF-κB could not affect the production of TNF-α but decreased other inflammatory mediators, such as IL-1β, IL-6, iNOS and COX2 [ 41 , 42 , 43 ]. It has also been reported that selective inhibition of p38 or JNK downregulated TNF-α as well as other inflammatory mediators [ 44 ].…”
Section: Resultsmentioning
confidence: 84%
“…BMMs were seeded into 96-well plates (8 × 10 3 cells/well) in triplicate, and cultured in complete α-MEM (10% FBS and 30 ng/ml M-CSF) with isorhamnetin 3-O-neohesperidoside at a concentration (0.5, 1, 5, 10, 25, 50, 100 and 200 μM) for 24, 72, and 96 hrs. Ten microliters of CCK-8 solution was added to each well for 4 h, following which cell viability was determined by measuring the absorbance at 450 nm, as reported previously 16 . www.nature.com/scientificreports www.nature.com/scientificreports/ Osteoclast differentiation and TRAP staining.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Osteoclast differentiation and TRAP staining. As reported previously 16 , BMMs were seeded into 96-well plates (1 × 10 4 cells/well). After 24 h, the cells were cultured in α-MEM (10% FBS, 30 ng/ml M-CSF and 50 ng/mL RANKL) with isorhamnetin 3-O-neohesperidoside at a concentration gradient (0, 1, 5, 25 and 50 μM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation